2007
DOI: 10.1007/s10549-007-9621-9
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and risk of breast cancer in carriers of mutations in BRCA1 or BRCA2 aged less than 50 years

Abstract: Background-Cigarette smoke contains compounds that may damage DNA, and the repair of damage may be impaired in women with germline mutations in BRCA1 or BRCA2. However, the effect of cigarette smoking on breast cancer risk in mutation carriers is the subject of conflicting reports. We have examined the relation between smoking and breast cancer risk in non-Hispanic white women under the age of 50 years who carry a deleterious mutation in BRCA1 or BRCA2.Methods-We conducted a case-control study using data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Two other studies did not find interaction between smoking and family history ( Cui et al , 2006 ; Gaudet et al , 2013 ), but stratified estimates were not shown; therefore, it is unknown whether the estimates were consistent with our findings. In women at high risk of a specific type of familial breast cancer, BRCA1/BRCA2 mutation carriers, current smoking was not associated with increased risk ( Ghadirian et al , 2004 ; Nkondjock et al , 2006 ; Ginsburg et al , 2009 ), which is consistent with our finding of no smoking-associated risk among women with a family history, although smoking was associated with increased risk among mutation carriers in one study ( Breast Cancer Family Registry et al , 2008 ). The potential mechanism that would result in smoking-associated risk only among those without a family history of breast cancer is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…Two other studies did not find interaction between smoking and family history ( Cui et al , 2006 ; Gaudet et al , 2013 ), but stratified estimates were not shown; therefore, it is unknown whether the estimates were consistent with our findings. In women at high risk of a specific type of familial breast cancer, BRCA1/BRCA2 mutation carriers, current smoking was not associated with increased risk ( Ghadirian et al , 2004 ; Nkondjock et al , 2006 ; Ginsburg et al , 2009 ), which is consistent with our finding of no smoking-associated risk among women with a family history, although smoking was associated with increased risk among mutation carriers in one study ( Breast Cancer Family Registry et al , 2008 ). The potential mechanism that would result in smoking-associated risk only among those without a family history of breast cancer is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…In three studies, researchers reported significant interactions, with one showing increased breast cancer risk with smoking only among those with a positive family history [ 39 ], whereas two demonstrated that breast cancer risk was raised only among those with no family history [ 15 , 18 ]. Increased risk of breast cancer with smoking has also been seen in some [ 40 , 41 ], but not all ( see review [ 1 ] and a large meta-analysis [ 41 ]), studies of BRCA1/2 carriers (or by proxy, women with three or more first-degree relatives with breast or ovarian cancer [ 42 ]). There are also reports of significant interactions with smoking and polymorphisms in carcinogen metabolism genes NAT2 [ 43 ] and CYP1A1 [ 44 , 45 ] as well as breast cancer susceptibility single-nucleotide polymorphisms [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of the prospective studies conducted in the general population suggested a 13% increased risk of breast cancer (95% CI 1.09–1.17) for current smokers, compared to never smokers [39]. Regarding whether cigarette smoking is a risk factor for cancer in BRCA mutation carriers within this high-risk population, a number of earlier reports, including two from our group, have yielded inconclusive results, and have been limited by small sample sizes and retrospective study designs, which are vulnerable to selection bias and information bias [40,41,42,43,44,45]. In a recent prospective analysis of BRCA mutation carriers that included 26,711 person-years of follow-up and 700 incident cancers (428 breast cancers, 109 ovarian cancers), tobacco smoking was a risk factor for BRCA -associated cancer in general, including cancers of the breast and ovary [46].…”
Section: Modifying Factors For Brca-associated Breast Cancermentioning
confidence: 99%